Evolution Trend of Water Resources in Xijiang River Basin - SHI Xufan; YAO Zhibin; ZHANG Can (Renmin Zhujiang)
Influenced by natural geographical factors and human activities, the evolution of water resources has a certain regularity and periodicity. In order to understand the evolution trend of water resources in Xijiang River Basin, based on the data of the third water resources survey and evaluation in the Pearl River area, the annual precipitation, evaporation, and water resources in Xijiang River Basin were assessed, and the impact of precipitation and human activities on the water resources situation was analyzed by using the moving average method, Mann-Kendall trend test, and quantitative assessment method. The results indicate that the annual precipitation and annual runoff in Xijiang River Basin show an insignificant upward trend of fluctuation. The annual precipitation of the basin is consistent with the annual runoff variation of Gaoyao Station, including three dry phases and three abundant water phases. The impact of precipitation on runoff in four stages from 1971 to 2016 ranges from -9.58 billion to 2.12 billion cubic meters. The direct impact of human activities makes the runoff decrease, and the influence increases gradually. The indirect impact of human activities increases runoff. The conclusion of this analysis provides an important foundation for the formulation of water resource planning, the development and utilization of water resources, and the construction of major water conservancy projects in Xijiang River Basin.